Optimized 3D ultrashort echo time pulmonary MRI - Johnson, Kevin M.; Fain, Sean B.; Schiebler, Mark L.; Nagle, Scott (Magnetic resonance in medicine, 2013)
Purpose To optimize 3D radial ultrashort echo time MRI for high resolution whole‐lung imaging. Methods 3D radial ultrashort echo time was implemented on a 3T scanner to investigate the effects of: (1) limited field‐of‐view excitation, (2) variable density readouts, and (3) radial oversampling. Improvements in noise performance and spatial resolution were assessed through simulation and phantom studies. Their effects on lung and airway visualization in five healthy male human subjects (mean age 32 years) were compared qualitatively through blinded ordinal scoring by two cardiothoracic radiologists using a nonparametric Friedman test (P < 0.05). Relative signal difference between endobronchial air and adjacent lung tissue, normalized to nearby vessel, was used as a surrogate for lung tissue signal. Quantitative measures were compared using the paired Student's t‐test (P < 0.05). Finally, clinical feasibility was investigated in a patient with interstitial fibrosis. Results Simulation and phantom studies showed up to 67% improvement in SNR and reduced blurring for short T2* species using all three optimizations. In vivo images showed decreased artifacts and improved lung tissue and airway visualization both qualitatively and quantitatively. Conclusion The use of limited field‐of‐view excitation, variable readout gradients, and radial oversampling significantly improve the technical quality of 3D radial ultrashort echo time lung images. Magn Reson Med 70:1241–1250, 2013. © 2012 Wiley Periodicals, Inc.